STRATEGI KOMUNIKASI PUBLIC RELATIONS PT PEGADAIAN CABANG SERPONG DALAM MEMBANGUN BRAND AWARENESS PADA PRODUK TABUNGAN EMAS - Rangga Adyatama Novaliano; Agung Raharjo (Journal of Research and Publication Innovation, 2025)
PT Pegadaian (Persero) is a state-owned institution that works in the field of credit services with several products they have such as Gold Savings products. However, the social phenomenon that occurs is that there are still many people who do not know about these products. This research uses qualitative methods with data collection techniques through interviews, observation, and documentation. The results showed that PT Pegadaian Serpong Branch implemented various effective communication strategies, such as promotion through social activities, and training for employees to improve service quality. These strategies succeeded in increasing brand awareness and the number of customers using Gold Savings products. Thus, this study concludes that the right Public Relations communication strategy can increase Brand Awareness and strengthen the company's image in the eyes of consumers